(3SjQI SjO GdYHGOs - (3eMeO GdTGejs
(3ChdgG (B:s
(3GdHGH GdChd ajeG Ydeg Udi Gddg Ydjg hSde dYGFTI QVi Gddg JYGdi YfgG deG hYcJ s
(3BNQgG (B:s
(3hMjf JeSjf SHMGf Gddg hHMeOg hdGbhg EdG HGddg eG TGA Gddg cGf heGde jTGA de jcf JeJ s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdXGgQjI s
Keywords: (3GdMOjK h GdeUWdMs